ANALISIS PERANCANGAN PROYEK MESIN PENGUPAS KULIT KACANG TANAH - Febriansyah, Ferdi; Saleh, Agus (Jurnal Mahasiswa Terapan; Vol 1 No 1 (2024): Jurnal Mahasiswa Terapan, 2024)
Peanut peeling is mostly done manually which requires more labor and time so that the results are not efficient, to make it easier for peanut farmers to process peanuts, a peanut peeling machine was designed. A peanut skin peeling machine is a machine used to peel peanut skins so that the skin and contents of the peanuts are separated. Peeling is done by a peeling knife consisting of a shaft and a plate connected by welding. The way this machine works is by inserting dry peanuts into the funnel then the peeling knife will break the peanuts by means of the shaft pushing the peanuts into a network of steel bars that have been arranged horizontally. Then the peeling results will fall through the sorter in the form of peanut skins and contents that are still mixed.